Ultrasound as a method for early diagnosis of breast pathology - Santos, Rute; Ribeiro, Ana Raquel; Marques, Daniela (MDPI, 2023)
Introduction: Ultrasound is a non-invasive, low-cost technique that does not use ionising radiation and provides a “real-time” image, and for these reasons, this method is ideal in several situations. Purpose: To demonstrate breast ultrasound evaluation as a first-line diagnostic method and to evaluate the variation of breast characteristics with age. Material and Methods: A total of 105 women with a mean age of 30 years participated and were divided into three age groups: 18–39, 40–59, and 60–79 years, excluding participants subject to mastectomy. After completing the informed consent, all participants answered personal and sociodemographic questions, such as personal and family history, menstrual cycle, pregnancy, ultrasound, and mammography, among others. They were then submitted to a bilateral breast ultrasound examination. Subsequently, all the images and their data were analysed, and a technical report of the examination was given to all the participants. Results: A total of 105 women with a mean age of 30 years participated, 58 of whom underwent the examination for the first time. In 31, changes (of which only 7 were known) were diagnosed. It was verified that, according to age group, the density of the breast stroma varied; older women have less breast density. Conclusions: Ultrasound is a good method for breast evaluation and can be considered important for the early evaluation of breast pathology and follow-up of the pathology.
Keywords: Ultrasound; Breast; Breast pathology; Ultrasound screening; Ultrassonografia; Mama; Patologia da mama; Ultrassonografia de rastreio